Does cartilage volume or thickness distinguish knees with and without mild radiographic osteoarthritis? The Framingham Study. Issue 01 (4th February 2009) - Reichenbach, S; Yang, M; Eckstein, F; Niu, J; Hunter, D J; McLennan, C E; Guermazi, A; Roemer, F; Hudelmaier, M; Aliabadi, P; Felson, D T
Abstract : Objectives: To examine whether the quantity of cartilage or semiquantitative scores actually differ in knees with mild radiographic osteoarthritis compared with knees without osteoarthritis. Methods: Framingham Osteoarthritis Study participants had knee tibiofemoral magnetic resonance imaging-based measurements of cartilage. Using three-dimensional FLASH-water excitation sequences, cartilage volume, thickness and subregional cartilage thickness were measured and cartilage scored semiquantitatively (using the whole-organ magnetic resonance imaging score; WORMS). Using weight-bearing radiographs, mild osteoarthritis was defined as Kellgren/Lawrence (K/L) grade 2 and non-osteoarthritis as K/L grade 0. Differences between osteoarthritis and non-osteoarthritis knees in median cartilage measurements were tested using the Wilcoxon rank sum test. Results: Among 948 participants (one knee each), neither cartilage volume nor regional thickness were different in mild versus non-osteoarthritis knees. In mild osteoarthritis, cartilage erosions in focal areas were missed when cartilage was quantified over large regions such as the medial tibia. For some but not all subregions of cartilage, especially among men, cartilage thickness was lower (p<0.05) in mild osteoarthritis than non-osteoarthritis knees. Because semiquantitative scores captured focal erosions, median WORMS scores were higher in mild osteoarthritis than non-osteoarthritis (all p<0.05). In moderate/severe osteoarthritis (K/L grades 3 or 4), osteoarthritis knees had much lower cartilage thickness and higher WORMS scores than knees without osteoarthritis. Conclusions: In mild osteoarthritis, the focal loss of cartilage is missed by quantitative measures of cartilage volume or thickness over broad areas. Regional cartilage volume and thickness (eg, medial tibia) are not different in mild osteoarthritis versus non-osteoarthritis. Subregional thickness may be decreased in mild osteoarthritis. Semiquantitative scoring that assesses focal cartilage damage differentiates mild osteoarthritis from non-osteoarthritis.